Kajian Tafsir al-Mishbah Karya Muhammad Quraish Shihab - Abdul Aziz; Diayah Sofarwati (LP3M UNZAH GENGGONG, 2021)
Abstract: Tafsir Al-Mishbah by M. Quraish Shihab, is a contemporary interpretation written by an Indonesian commentator. Tafsir Al-Mishbah when viewed from the point of view of the target and order of the interpreted verses are compiled using the Tahlily method, in terms of the source of the interpretation, including the interpretation of bi al-Ra'yi (bi al-Dirayah bi al-Ma'qul), in terms of the way of explanation on the interpretation of the verses of the Qur'an, using the Muqorin (Comparative) method, in terms of the breadth of the explanation of the interpretation, then using the itnabi method. The style of Tafsir Al-Mishbah, namely the Lughawi/Adabi interpretation, is also Ijtima'i. Keywords: Quraish Shihab, Al-Mishbah, Tafsir, Methods, Patterns of interpretation.